DEPRESCRIBING – A NECESSARY DISCUSSION FOR THE INTEGRAL HEALTH OF THE ELDERLY - Scremin, Marlete; Carl Silva, Jean; Henrique Pereira Sena, Kaio; Carpegiane Ornelas Deles, Bruno; Alencar Froes, Karine; Sérgio David de Castro, Paulo; Gusmão Soares, Raquel; Ribeiro de Andrade Neto, Gregório; Veloso Quintino Borborema, Francine; Falcão de Ornelas, Haline; Mendes de Oliveira, Jaqueline; Kariny Soares Oliveira, Maricy; et al. (Health and Society, 2026)
The present study aims to understand the deprescribing process among elderly patients. A theoretical-reflective study was conducted based on the concepts of health education and health promotion. In the face of technological advances in the health area, increased income, urbanization and many other social advances that culminated in the increase in the life expectancy of the population, another synergistic phenomenon was the epidemiological transition, causing an increase in the number of chronic-non-communicable diseases, requiring health services and professionals to act effectively and comprehensively in the face of this new paradigm in population health.  In this sense, medications are an important support strategy, however, when this use is unsystematic, exaggerated and indiscriminate, it can substantially harm the health of the elderly, in this discussion, deprescription presents itself as an important clinical tool to reduce the health risks of these individuals, however, there are barriers of training, resistance of family members and professionals,  Because the latter are often trained in a biologist and curative model, in a logic that for each complaint a drug is chosen, thus, efforts are needed from the country’s training bodies to train professionals who are committed to presenting other possibilities to patients, which often bring less risk and better clinical outcomes.